“OMNIA IN CARITATE”: MODEL PELAYANAN PASTORAL TERHADAP ORANG MISKIN DI TENGAH PENDEMI COVID-19 - Florensia Imelda Seran; Soteris Seperuri Tanggul; Benedikta Suryani (Jurnal Pelayanan Pastoral, 2022)
This article concentrates on analyzing the pastoral model in the spirit of “Omnia in caritate” as one of the important responses to the economic impact of the spread of COVID-19 which has caused many people or people to fall into poverty. The main problem highlighted in this research is the phenomenon of church service which is still conceptual-theoretical and linturgicentric. This means that the ministry of the Church is still limited to teaching and dwelling on pastoral theological concepts, and still concentrating on ritual piety centered on the altar. The pastoral ministry of the Church has not yet reached the concrete market of life. Using document studies, this article concludes that pastoral care inspired by the spirit of omnia in caritate is a contextual and relevant model of pastoral care amid a pandemic. The omnia in caritate spirit is able to reach people affected by the COVID-19 pandemic, especially those who fall into poverty.